2022
DOI: 10.3390/children9101525
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound (CEUS) as an Ancillary Imaging Test for Confirmation of Brain Death in an Infant: A Case Report

Abstract: The practices for determining brain death are based on clinical criteria and vary immensely across countries. Cerebral angiography and perfusion scintigraphy are the most commonly used ancillary imaging tests for brain death confirmation in children; however, they both share similar shortcomings. Hence, contrast-enhanced ultrasound (CEUS) as a relatively inexpensive, easily accessible, and easy-to-perform technique has been proposed as an ancillary imaging test for brain death confirmation. CEUS has establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies on adult populations have shown that the rate of inconclusive Doppler US examinations for determining cerebral circulatory arrest significantly decreases when CEUSs are performed [ 81 , 83 ]. A couple of reports already demonstrated that the CEUS can also be reliably used as an ancillary imaging test for the confirmation of brain death in neonates [ 37 , 84 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Studies on adult populations have shown that the rate of inconclusive Doppler US examinations for determining cerebral circulatory arrest significantly decreases when CEUSs are performed [ 81 , 83 ]. A couple of reports already demonstrated that the CEUS can also be reliably used as an ancillary imaging test for the confirmation of brain death in neonates [ 37 , 84 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%